Effect of aspirin in patients with established asymptomatic carotid atherosclerosis: A systematic review and meta-analysis - Hu, Xianjin; Hu, Yao; Sun, Xiankun; Li, Ying; Zhu, Ye (Frontiers in Pharmacology, 2022)
Background: Aspirin is widely used as an antiplatelet agent for secondary prevention in patients with atherosclerotic cardiovascular disease. However, it remains unclear whether aspirin can prevent the progression of carotid atherosclerosis or reduce vascular events and all-cause death. Methods: We performed a meta-analysis of the effect of aspirin in asymptomatic carotid atherosclerotic patients. Electronic databases including Pubmed, EMBase, ISI Web, Medline, Cochrane, and clinicaltrial.gov were searched for relevant randomized controlled trials. A total of five studies (841 individuals, 2145 person-years) were included in this study. Two reviewers independently performed the study assessment and data extraction. Forest plots were used to assess the efficacy of aspirin. Egger’s test was used to evaluate publication bias. Results: Aspirin did not alleviate the progression of carotid intima-media thickness (cIMT) compared with control patients (WMD: −0.05 mm, 95% confidence interval 95%CI]: −0.12, 0.03). In subset analysis, aspirin was only associated with regression of cIMT when compared with the empty/placebo group (WMD: −0.10 mm, 95%CI: −0.18, −0.02). In type 2 diabetes mellitus, there were no statistical significance between groups (WMD: 0.10 mm, 95%CI: −0.31, 0.50). For the main vascular events and all-cause death, there were no differences between the aspirin group (RR: 0.73, 95%CI: 0.41, 1.31) and the control group (RR: 0.88, 95%CI: 0.41, 1.90). For outcome events, similar results were observed when patients were classified by different cIMT value (P > 0.05). The risk of gastrointestinal bleeding was similar between participants receiving and not receiving aspirin therapy (RR: 1.04, 95%CI: 0.07, 16.46). Conclusion: In patients with asymptomatic carotid atherosclerosis, low-dose aspirin may slightly alleviate the progression of cIMT, but does not reduce vascular events and all-cause death.